Suitable rootstocks can alleviate the effects of heat stress on pepper plants - Gisbert-Mullor, Ramón; Gara-Padilla, Yaiza; Martínez-Cuenca, Mary-Rus; López-Galarza, Salvador; Calatayud, Ángeles (Elsevier, 2021)
In this study, different pepper rootstocks are tested for their ability to overcome heat stress situations. This work aims to evaluate: (I) the physiological mechanisms that occur during long heat stress periods (7 days) under controlled conditions in a pepper variety grafted onto accessions; (II) the heat stress behaviour of these grafted pepper plants under greenhouse conditions in terms of marketable yields. For this purpose, plants of Lamuyo-type sweet pepper ‘Herminio F1’ (VA), grafted onto six accessions (VA/A25, VA/A31, VA/A34, VA/A52, VA/A57, VA/A6), and a self-grafted variety (VA/VA) were grown under controlled conditions in growth chambers (28/24°C, day/night temperatures and 38/24°C for control and heat stress, respectively) and under greenhouse conditions (38/24°C). For the controlled conditions, relative growth rate, leaf area, electrolyte leakage, chlorophyll a fluorescence and heat shock proteins were determined. For the greenhouse conditions, fresh and dry weigh, electrolyte leakage and fruit yield were determined. Our results confirmed that grafting a pepper cultivar onto appropriate rootstocks such as A6, A25 and A57 can overcome the negative effects of heat stress conditions with a higher relative growth rate, leaf area and Fv/Fm, and lower electrolyte leakage under the controlled conditions, and with higher marketable yields under the greenhouse conditions.